2011
DOI: 10.1016/j.hivar.2011.04.001
|View full text |Cite
|
Sign up to set email alerts
|

A study of clinical profile of HIV positive patients with neurological manifestations

Abstract: a b s t r a c tBackground: Central nervous system (CNS) is among the most frequent and serious target of HIV infection in patients with profound immunosuppression. CNS problems occur mainly due to either primary pathologic process of HIV or secondary to opportunistic infection and neoplasm. Aims and objectives: To study the clinical and investigation profile in diagnosis of HIV patients with CNS manifestation. To correlate CD 4 levels with CNS opportunistic infections. Materials and methods: A prospective obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 5 publications
5
13
0
Order By: Relevance
“…This is similar to the findings of other studies by Shripad R Kausadikar et al, 13 MD Solu et al 14 and Himanshu M Rana. 15 In our study tuberculous meningitis was the most common infection with 16 patients (35.6%), out of which 4 patients also had intracranial tuberculoma. Next common infections was cryptococcal meningitis in 9 patients (20%) and toxoplasmosis in 6 patients (13.3%).…”
Section: Symptomsmentioning
confidence: 45%
See 2 more Smart Citations
“…This is similar to the findings of other studies by Shripad R Kausadikar et al, 13 MD Solu et al 14 and Himanshu M Rana. 15 In our study tuberculous meningitis was the most common infection with 16 patients (35.6%), out of which 4 patients also had intracranial tuberculoma. Next common infections was cryptococcal meningitis in 9 patients (20%) and toxoplasmosis in 6 patients (13.3%).…”
Section: Symptomsmentioning
confidence: 45%
“…In a study from NEIGRIHMS, Shillong, Shri Ram Sharma et al 16 found Tuberculous meningitis (43.95%) to be more common than cryptococcal meningitis (14.2%) followed by toxoplasmosis (2.19%). Similarly, Himanshu M Rana et al 15 found tuberculous meningitis (34%) more common than Cryptococcal meningitis (14%) and cerebral toxoplasmosis (10%). Attili Venkata Satya et al 17 also found the same pattern.…”
Section: Symptomsmentioning
confidence: 84%
See 1 more Smart Citation
“…NORMAL ATROPHY HIVE TOXO PML CNS LYM TB CRYPTO INFARCT HYDROC VASCU CMV HSV BAC PRESENT ABSENT PRESENT ABSENT PRESENT ABSENT PRESENT ABSENT PRESENT ABSENT PRESENT ABSENT PRESENT ABSENT PRESENT ABSENT PRESENT ABSENT PRESENT ABSENT PRESENT ABSENT PRESENT ABSENT PRESENT ABSENT PRESENT ABSENT CT POSITIVE 13 0 2 6 4 1 5 2 3 0 2 1 3 2 0 0 5 3 1 0 0 0 0 0 1 0 0 0 CT NEGATIVE 0 41 0 46 4 45 1 46 1 50 0 51 2 47 2 52 0 46 0 53 1 53 2 52 1 52 2 The most common neurological abnormality in patients imaged with CT scan and MRI in our study was HIV encephalopathy (n=8) and the most common opportunistic infections were toxoplasmosis (n=6) and tuberculosis (n=5). In studies by Patel ML et al, Kausadikar SR et al, Rana HM et al [10] , Mahajan et al [11] and Lanjewar DN et al [12] , tuberculosis was the most common cause of opportunistic infections. Normally, when tubercle bacilli reach lung alveoli, alveolar macrophages ingests them.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Cryptococcus neoformans being an important cause among etiologies causing fungal meningitis. [6] With the availability of antiretroviral therapy (ART) at lower cost, the clinical profile of HIV disease in India is now changing to include drug-related toxicities and immune reconstitution syndrome.…”
Section: Introductionmentioning
confidence: 99%